How does retirement affect health? - Stefanie Behncke (Institute for the Study of Labor (IZA), 2009)
This paper investigates the effects of retirement on various health outcomes. Data stem from the first three waves of the English Longitudinal Study of Ageing (ELSA). With this informative data, non-parametric matching methods can be applied to identify causal effects. It is found that retirement significantly increases the risk of being diagnosed with a chronic condition. In particular, it raises the risk of developing a cardiovascular disease and being diagnosed with cancer. Estimates also indicate that retirement has quite diverse effects for different individuals.
urn:nbn:de:101:1-20090703155
Keywords: I10; J14; J26; 360; Retirement; health; matching methods; ELSA; Altersgrenze; Gesundheit; Alte Menschen; Großbritannien